A systematic review of qualitative studies on adjusting after stroke: lessons for the study of resilience. (April 2014) - Sarre, Sophie; Redlich, Cara; Tinker, Anthea; Sadler, Euan; Bhalla, Ajay; McKevitt, Christopher
Abstract Purpose: To synthesize qualitative studies on adjusting after stroke, from stroke survivors' and carers' perspectives, and to outline their potential contribution to an understanding of resilience. Methods: A systematic review of qualitative studies in peer reviewed journals from 1990 to 2011 was undertaken. Findings from selected studies were summarized and synthesized and then considered alongside studies of resilience. Results: Forty studies were identified as suitable. These suggested that the impact of stroke was felt on many dimensions of experience, and that the boundaries between these were permeable. Nor was stroke as an adverse "event" temporally bounded. Adjustment was often marked by setbacks and new challenges over time. Participants identified personal characteristics as key, but also employed practical and mental strategies in their efforts to adjust. Relationships and structural factors also influenced adjustment after stroke. Conclusions: The impacts of stroke and the processes of adjusting to it unfold over time. This presents a new challenge for resilience research. Processes of adjustment, like resilience, draw on personal, inter-personal and structural resources. But the reviewed studies point to the importance of an emic perspective on adversity, social support, and what constitutes a "good" outcome when researching resilience, and to a greater focus on embodiment. Implications for Rehabilitation Stroke is a sudden onset condition which for around a third of people has long-term consequences. Stroke can cause a variety of physical and cognitive impairments, some of which may not be obvious to an outsider. As well as physical functioning, stroke can have a profound effect on survivors' sense of self and on their relationships. Stroke survivors' accounts suggest that relationships (including relationships with health care professionals) and structural factors (such as access to health services, employment possibilities and welfare systems) mediate efforts to adjust after stroke. While there is considerable overlap between notions of adjustment and resilience, the experiences of stroke survivors suggest further issues that need to be addressed in order to gain a more comprehensive understanding of resilience.